Composition and Antimicrobial Activity of Essential Oil from the Flower of Rhododendron luteum Sweet - Usta, Asu; Yayli, Busra; Kahrinman, Nuran; Alpay Karaoglu, Sengul; Yayli, Nurettin (Asian Journal of Chemistry, 2011)
Essential oil from air-dried flower of Rhododendron luteum Sweet (Ericaceae), was obtained by hydrodistillation in a Clevenger-type apparatus and analyzed by GC-MS and GC-FID. Sixty-four components were identified in the oil. The most abundant components in the investigated essential oil from the flower of R. luteum was found to be a-cadinol (8.9 %), d-cadinene (7.6 %), a-terpineol (7.2 %), benzyl salicylate (6.2 %), a-muurolene (4.1 %) and 1,6-germacradien-5b-ol (3.4 %). The antimicrobial activity of the isolated essential oil was investigated and it showed moderate antimicrobial activity against Serratia marcescens, Enterococcus faecalis and Staphylococcus aureus, but no antifungal activity was observed against yeast like fungi.